Instrumen Asesmen Bagi Pendidik Dalam Proses Pembelajaran Biologi Berbasis Problem Based Learning: (Assessment Instruments for Teacher in Biology Learning Process by Problem Based Learning) - Meri Suriyani; Try Susanti; Darma Putra (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
This study aims to produce PBL based assessment instruments (problem based learning) that are made to measure learning process for educators, in this case, the researcher will focus on the discussion about attitude. This research is an instrument development research adapted from ADDIE model, this model there are 5 stages: analysis, design, development, implementation and evaluation. Data collection and data analysis using different questionnaires and given to expert / expert teams and users of assessment instruments. To find out the feasibility of the instrument, the questionnaire was given to 3 expert teams / experts and got the score category 88%, then the score result on the assessment instrument is